Modulation of the coordination environment: a convenient approach to tailor magnetic anisotropy in seven coordinate Co(ii) complexes. Issue 4 (16th November 2015) - Dey, Mamon; Dutta, Snigdha; Sarma, Bipul; Deka, Ramesh Ch.; Gogoi, Nayanmoni
Abstract : Subtle modulation of the coordination environment in seven coordinate Co(ii ) complexes leads to a remarkable deviation in the axial zero field splitting parameter ( D ) in a predictable fashion. Abstract : The possibility of controlling magnetic anisotropy by tuning contribution of second order perturbation to spin–orbit coupling through modulation of the coordination environment is investigated. Subtle variation of the coordination environment triggers a remarkable deviation in the axial zero field splitting parameter of seven coordinate Co(ii ) complexes.